30-day journey with Martin Luther King Jr. - King, Martin Luther, Jr., 1929-1968 (30-day journey, 2019)
Through brief daily readings and reflections, the 30-Day Journey series invites readers to be inspired and transformed. Martin Luther King Jr. led a country from division, racism, and hate toward unity and equality. Whether you are familiar with MLK's writings or are encountering them for the first time, this journey provides the perfect way to engage the thought of this hero of the civil rights movement.